PERFORMANCE ANALYSIS OF LOOSE BIO MASS BRIQUTTES FROM AGRO AND FORESTRY WASTE - R.Raguraman,; I.Duraimurugan,; K.Prakash,; C.Ezhilarasan, (International Journal of Psychosocial Rehabilitation, 2020)
The substitute of this non-renewable source with natural Waste would lesser the larger pollution of the world. The Agricultural and plant scraps converted to valuable biomass briquettes, which is the substitution of coal. The biomass wastes like Banana leaves saw dust, rice shell, coffee shell, Groundnut shell that are collected, pressed and compacted as bio waste briquettes, which can be transported and used to produce heat. Bio waste is the unique form having lower mass density large transportation and storage cost and not able to used as fuel. Densifying biomass wastes by briquetting method helps to minimize the storage handling problems and improved the colorific value of bio waste combustible fuel. After that calorific value, fixed carbon content, Ash content, moisture content, volatile matter for different composition of biomass briquettes were analyzed and investigated. It was observed that moisture content increases volatile matter also increases it reduce calorific value. Briquette-2 ash content 3 to 4 times lower than the other briquettes and it has 19MJ/kg. It can reduce the overall pollution when compared the other fossil fuel combustion. Saw dust briquettes easy to dry and better utility among various bio-waste briquettes.